(Design and Technical Testing for centrifuge for degumming and Vacuum Deodorizer for Palm kernel Oil (PKO)) - Alamsyah, Rizal; -, Rienoviar; Mitha Mala, Dheni (Balai Besar Industri Agro, 2007)
Deodorizing and reaction time of degumming are some of the most important factors that can affect the quality refined vegetable oils or its derivatives. The results of unit operations in doedorizing and degumming give low viability of product especially produced by vegetable oils smallholder industry in Indonesia. To increase quality of those and income producer there is a need to enhance process by introducing appropriate equipments. This study was devoted in designing and testing centrifuge for degumming of crude vegetable oils (Palm kernel oil) and vacuum deodorizer using jet pump for refining oils. The maximum capacity of sentifuge constructed is 12 liters and it was equipped with four container and 1 horse power of induction motor. The performance test of centrifuge showed reaction time for degumming was two hours with maximum impurities or gums (7%). This reaction time is shorter than those of conventional degumming process using settling tank e.g all night reaction time. Deodorizer reactor has capacity of 40 liters oil processed, and it is generated with 1,1 hp of induction motor. steam from small boiler unit was introduced to the doedorized tank to reduces impurities and free fatty acid (FFA). The reactor was equipped with metal heater element of 5000 watt which immersed in silicon oil as heating medium and it was covered by insulator. The reaction temperature of deodorizing process was 160 degree celcius. Palm kernel oil quality processed by vacuum deodorizer tested e.g. free fatty acid (FFA) was 0,03%, peroxide number was 3,03 meq/kg, moisture content was 0,94%,anisidin number was 3,97, and color were yellow and red (0,4 and 7). It means that those results of refined palm kernel oil caracteristics meet the standard required.